Nutrient removal from wastewater by integrated attached growth bioreactor - Ezechi, E.H. (Academic Journals Inc., 2016)
Water body deterioration caused by natural and anthropogenic activities has been a source of concern for regulating agencies. Several problems such as eutrophication and blue baby syndrome are caused by the excessive presence of nutrients within the aquatic biota. This also presents danger to the benthic community. In this study, an integrated aerobic/anoxic attached growth bioreactor was evaluated for its performance in removing nutrients (ammonia and nitrate) from simulated synthetic low and medium strength domestic wastewater. The experiment was conducted in two stages. Stage 1 consists of ammonia concentration of about 16 mg L-1 whereas, stage 2 consists of ammonia concentration of about 26 mg L-1. Bioreactor performance was also evaluated at two different Hydraulic Retention Time (HRT) of 7.2 and 12 days, respectively. Seed sludge was collected from a domestic sewage treatment plant. The performance of the bioreactor was monitored every two days with samples collected from aerobic compartment, anoxic compartment and net effluent. At HRT of 12 days, results at steady state condition shows that an effluent ammonia concentration of about 0.33 mg L-1 was obtained in stage 1. Steady state effluent ammonia concentration slightly increased to 0.65 mg L-1 in stage 2. Steady state effluent nitrate concentration (0.2 and 0.55 mg L-1) was low in both stages 1 and 2. In both stages 1 and 2, ammonia removal reached 98. The HRT was found to exert slight influence in nutrient removal using the integrated bioreactor. At HRT of 7.2 and 12 days, effluent ammonia concentration of 1.1 and 0.6 mg L-1 was obtained, whereas effluent nitrate was in the range of 0.55 and 0.22 mg L-1, respectively. Chemical Oxygen Demand (COD) was also monitored at steady states and was found below 20 mg L-1 in both stages 1 and 2 at HRT of 12 days. This study, therefore demonstrates the capacity of an integrated bioreactor to mitigate the enormous challenge of water body deterioration and toxicity caused by indiscriminate discharge of polluted wastewater. Â© 2016 Academic Journals Inc.